Optimizing PI Controller Performance in Ultra Step-Up Converters Using Particle Swarm Optimization - Saputra, Gilang Rizki; Purwanto, Era; Rusli, Muhammad Rizani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The development of electric vehicles (EVs) drives the need for high-voltage ratio DC-DC step-up converters capable of connecting low-voltage battery power sources to electric drive systems and auxiliary systems requiring high voltages. This study proposes a non-isolated ultra step-up converter incorporating a diode–capacitor–inductor (D–C–L) unit at the input and a voltage multiplier cell (VMC) at the output. This topology achieves high voltage gain at low duty cycles while reducing voltage stress on semiconductor devices, enabling the use of lower-rated components and improving overall efficiency. Two control strategies were evaluated: a conventional Proportional–Integral (PI) controller and a PI controller tuned using Particle Swarm Optimization (PSO). MATLAB/Simulink simulations show that the PSO-PI controller outperforms the conventional PI, reducing overshoot from 21.7% to 8.7%, settling time from 227.78 ms to 117.78 ms, and voltage deviation during load changes from ±35 V to ±15 V. Recovery time under disturbances was also shortened from 0.4 s to as low as 0.15 s. These results confirm that PSO-based tuning enhances voltage regulation, transient performance, and robustness, making it a promising solution for ultra step-up converters in EV applications powered by 48 V sources.